The practice of crime prevention: design principles for more effective security governance - Berg, Julie (South African crime quarterly, 2011)
South Africa has had a comprehensive crime prevention policy agenda for some time in the form of the 1996 National Crime Prevention Strategy and the 1998 White Paper on Safety and Security. Despite this, prevention has remained very much a second cousin within the South African criminal justice family, notwithstanding the fact that there is widespread agreement that it warrants far more attention. In this article we briefly review some of the principal obstacles to effective crime prevention. Our understanding of ‘crime prevention’ is a broad one – it involves simply asking the question: How can we reduce the likelihood of this happening again? This question opens up a range of preventative possibilities. Whether they are of a socio-economic, environmental or law enforcement nature depends on the nature of the (crime) problem. On the basis of our analysis, we propose three design principles to be followed if we, South Africans are to establish crime prevention as a central focus of our security governance. These design principles articulate what might be thought of as ‘best thinking’ rather than ‘best practice’